2014
DOI: 10.1111/ajt.12520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rituximab Desensitization on Blood-Type-Incompatible Adult Living Donor Liver Transplantation: A Japanese Multicenter Study

Abstract: We evaluated the effects of rituximab prophylaxis on outcomes of ABO‐blood‐type‐incompatible living donor liver transplantation (ABO‐I LDLT) in 381 adult patients in the Japanese registry of ABO‐I LDLT. Patients underwent dual or triple immunosuppression with or without B cell desensitization therapies such as plasmapheresis, splenectomy, local infusion, intravenous immunoglobulin and rituximab. Era before 2005, intensive care unit‐bound status, high Model for End‐Stage Liver Disease score and absence of ritux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
178
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(194 citation statements)
references
References 18 publications
8
178
0
1
Order By: Relevance
“…A Japanese nationwide survey revealed that the 3-year survival rate increased from 30% to 80% after the introduction of RIT (17). A recent Japanese multicenter study revealed that the only risk factor for AMR was a DSZ protocol without RIT (5). In that study, the incidence of AMR decreased from 23.5% to 6.2% after the introduction of RIT.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…A Japanese nationwide survey revealed that the 3-year survival rate increased from 30% to 80% after the introduction of RIT (17). A recent Japanese multicenter study revealed that the only risk factor for AMR was a DSZ protocol without RIT (5). In that study, the incidence of AMR decreased from 23.5% to 6.2% after the introduction of RIT.…”
Section: Discussionmentioning
confidence: 93%
“…Several previous studies revealed that the effect of RIT on B cells in peripheral blood was very rapid, eliminating cells within 48-72 hours, and persisted for several months in transplant recipients (25). Furthermore, most data indicate that a single dose of RIT, as opposed to repeated doses, is sufficient for sustained suppression of B cells in peripheral blood (5,9,25,26). Consequently, repeated dosing of RIT may be unnecessary and may increase the risk of serious infection due to prolonged hypogammaglobulinemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this method, the donor pool has not significantly expanded because of the technical complexity of the surgery and ethical concerns. To further overcome organ shortage, ABO-incompatible LDLT was attempted and became successful after the implementation of rituximab, which decreased antibody-mediated rejection rates from 23.5% to 6.3%, as shown in a Japanese multicenter study [15] . The Milan criteria (solitary tumor < 5 cm, 2 or 3 tumors < 3 cm each, and absence of vascular invasion and extrahepatic metastasis) have been applied for the selection of candidates for liver transplantation [16][17][18] .…”
Section: Surgical Therapiesmentioning
confidence: 99%